(untitled) (Scientific journal of the Fergana State University, 2026)
This study examines the level of physical development among students of militarized schools (using the Temurbeklar School as an example) and general education schools. The main aim of the research is to compare the physical development indicators of students from different educational environments and to determine the impact of a military-disciplinary setting on their physical condition. Morphological and functional indicators such as height, weight, chest circumference, and body mass index were analyzed. The results revealed that students of the Temurbeklar School demonstrated a higher level of physical development, attributed to special training sessions, a strict daily regimen, and a military-oriented pedagogical approach. The findings can be applied to improve physical education systems and align health-promoting activities across both militarized and general education institutions.